Effect of Planned Teaching on Knowledge and Practices Regarding Selected Aspects of Quality of Life among Patients with Chronic Obstructive Pulmonary Disorder in Selected Hospital - Sawant, Suchita S; Ghaneka, Dr Jaishree; K Dasila, Dr Prabha; Rajan, Dr Sujeet (Innovational: Journal of Nursing and Healthcare, 2024)
Aim: The aim of the study was to evaluate effect of planned teaching on knowledge and practices regarding selected aspects of quality of life among patients with chronic obstructive pulmonary disorder. Materials and Methods: A descriptive evaluative research approach with one group pre-test and post-test research design was used for the study. The study was conducted at Mumbai district. The sample comprised 30 chronic obstructive pulmonary disease (COPD) patients who fulfilled the inclusion criteria for the sample selection. Sample was selected using non-probability convenient sampling technique. Data were analyzed using descriptive and inferential statistics. In that paired t-test to assess the effect of planned teaching on knowledge and practices regarding selected aspects of quality of life among patients with chronic obstructive pulmonary disorder. Results: The result of this study showed that the pre-test the mean of the knowledge obtained by the COPD patients was 9.03 and in post-test it increased to 23.33. It is evidence by the calculated t value 11 is greater than tabulated value 2.0 at 5% level of significance. The pre-test the mean of the practices obtained by the COPD patients was 5.46 and in post-test it increased to 13.73. It is evidence by the calculated t value 8 is greater than tabulated value 2.0 at 5% level of significance. Conclusion: Knowledge and practices in relation to selected aspects of quality of life among patients with COPD will improve their quality of life as COPD is chronic in nature. The planned teaching helped to increase the knowledge and practice of patients with COPD.